The Contemporary Meaning of Dawah Discussions in Tafsir AlQur’an Al-Kareem by Hafiz Abdul Salam Bin Muhammad - Mian Rameez Jawad; Dr, Sana Ullah Hussain (jihat-ul-islam, 2023)
Holy Quran is word of God and is a guideline for each and every person, in his or her every aspect of life, personal or social matters, in full capacity and for up to the last man to come before the day of Judgement. No one can get success in this world nor in the hereafter until or unless he fully follows and obey the commandments of Allah SWT being provided in Holy Quran . In this article different aspects of Dawat are being discussed mentioned in The Holy Quran, in the light of “Tafseer Al Quran Al Kareem by Hafiz Abdul Salam Bin Muhammad Bhutvi”. Importance of Dawa’a, its obligations, the characteristics of a Dae’e, impacts of Dawat on an individual and the society as a whole are taken into discussion. Also, the need for Dawat in today’s world is being discussed. The related elements which need to be given importance and to fully meet their necessity so as to make Dawa’a result oriented are also discussed in this article. Also, the intolerance found in the younger generation of this age, due to lack of religious education, social / political impacts etc. is taken into account and how much harm full this is for Dawat and its related elements.